La problematización en Foucault. Una metodología negativa en el taller de la historia. - Flavio Guglielmi (Perspectivas Metodológicas​)
The objective of this article is to review Foucault's main elaborations on the notion of problematization and its methodological difficulties, in order to later make a composition that can account for both instances. The work is divided into three sections; I) in the first, the origin and the space of emergence of the concept of problematization are determined; II) in the second, a typology of the different notions of problematization is made together with the different mentions of the term in different registers; III) Finally, a composition of the main characteristics highlighted in the previous points is developed.